2018 IEEE Information Theory Workshop (ITW) 2018
DOI: 10.1109/itw.2018.8613476
|View full text |Cite
|
Sign up to set email alerts
|

Performance Limits of Lattice Reduction over Imaginary Quadratic Fields with Applications to Compute-and-Forward

Abstract: Complex bases, along with direct-sums defined by rings of imaginary quadratic integers, induce algebraic lattices.In this work, we study such lattices and their reduction algorithms. First, when the lattice is spanned over a two dimensional basis, we show that the algebraic variant of Gauss's algorithm returns a basis that corresponds to the successive minima of the lattice in polynomial time if the chosen ring is Euclidean. Second, we extend the celebrated Lenstra-Lenstra-Lovász (LLL) reduction from over real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Napias first generalised the LLL algorithm to lattices spanned over imaginary quadratic rings and certain quaternion fields [6]; later Fieker, Pohst and Stehle investigated more fundamental properties of algebraic lattices [7], [8]. Recently Kim and Lee proposed an efficient LLL algorithm over bi-quadratic field whose quantization step requires a Euclidean domain [4], while our work on LLL over imaginary quadratic fields showed that a Euclidean domain is needed to make the algorithm convergent [9].…”
Section: Introductionmentioning
confidence: 95%
“…Napias first generalised the LLL algorithm to lattices spanned over imaginary quadratic rings and certain quaternion fields [6]; later Fieker, Pohst and Stehle investigated more fundamental properties of algebraic lattices [7], [8]. Recently Kim and Lee proposed an efficient LLL algorithm over bi-quadratic field whose quantization step requires a Euclidean domain [4], while our work on LLL over imaginary quadratic fields showed that a Euclidean domain is needed to make the algorithm convergent [9].…”
Section: Introductionmentioning
confidence: 95%
“…which are considered in most communication problems, is that there are some recently researches that consider as base field a general ring of algebraic integer, for example [23] and [24]. Moreover, the lattice reduction has also been generalized to a ring of imaginary quadratic integers [25] and only the rings from Q( √ −d), where d takes the values 1, 2, 3, 7 and 11 can be used to define Lovász condition [26].…”
Section: Introductionmentioning
confidence: 99%